Milk Composition of Etawah Crossedbred Goat Fed Forage and Leaves Pellet - Suranindyah, Yuni; Nurliyani, Nurliyani; Umami, Nafiatul (2013)
The study aimed to investigate the effect of substitution forage with leaves pellet on goat milk composition. Calliandra and Cassava leaves pellet were used in this study. Pellet substituted 12.25% of forage dry matter in the ration. The study used 9 lactating Etawah Crossed Bred goats, divided into 3 groups (Control, Treatment I and Treatment II). Feed in Control group consisted of grass, Calliandra and concentrate (21:49:30) of dry matter. In Treatment I and II the goat was given the similar ration, but 25% of Calliandra was substituted with Calliandra pellets and Cassava leaf pellets. Data were collected for 60 days, consisted of feed and nutrient consumption, milk composition (total solid, fat and protein content). The result showed there was a significant effect of substitution of forage with leave pellets on dry matter, crude protein, crude fiber and energy consumption (P< 0.05). Milk production, fat and protein was not affected by substitution. The study concluded there was no effect of feeding leaves pellets as forages substitution on the composition of goat milk